Perceived risk, trustworthiness, and security in E-wallet adoption: a study of DANA in West Sumatra - Difa Trevina Kinanti; Rahmiati Rahmiati (Universitas Negeri Padang, 2023)
This study aims to analyze the effect of perceived risk, perceived trust, perceived security on the intention to use DANA E-wallet in West Sumatra. The population in this study are people who use the DANA E-wallet in West Sumatra. This study involved 210 respondents as a sample. Data collection was carried out by distributing online questionnaires, and data was processed using SmartPLS software. The findings of this study indicate that (1) Perceived Risk has a negative but not significant effect on Perceived Trust, (2) Perceived Security has a positive and significant effect on Perceived Trust, (3) Perceived Risk has no negative and not significant effect on Intention to use, (4) ) Perceived Trust has a positive and significant effect on intention to use and (5) Perceived Security has a positive and significant effect on Intention to use.